Time and cold joint effect on chloride diffusion in concrete containing GGBFS under various loading conditions - Yang, H.; Lee, H.; Yang, K.; Ismail, Mohamed; Kwon, S. (Elsevier BV, 2018)
The stress due to volume change causes cracking in concrete, so that construction joint is intentionally prepared for an efficient construction and crack controlling in mass concrete structure. Cold joint means a weak joint area which may occur due to imperfect treatment of pre-placed concrete surface and delayed concrete delivery. Many researches have been performed for a quantitative evaluation of chloride ingress in cold joint concrete, which puts an emphasis on the more rapid penetration of chloride ions. The applied loading condition is one of the major reasons for concrete cracking and it also has a great effect on chloride penetration before the stage of cracking. Steel corrosion in concrete is accelerated when concrete cover has unsound area such as crack and cold joint. Chloride diffusion behavior varies with reduction of porosity and enhancement of hydrates, so called time effect on chloride diffusion. The effect of time and of cold joint on chloride diffusion is an important parameter for quantitative durability design for RC (Reinforced Concrete) structures exposed to various loading conditions. This paper investigates changes in chloride diffusion coefficient in cold joint concrete considering time effect and various loading conditions. Concrete samples with 0.6 of w/b (water to binder) and 40% replacement ratio of GGBFS (Ground Granulated Blast Furnace Slag) were prepared, and the chloride diffusion coefficients were measured for 1 year-cured concrete considering tensile and compressive loading conditions. The results were analyzed with the previous results in 91 days-cured concrete for evaluation of time effect. In the work, the time dependent chloride diffusion behaviors were quantitatively evaluated and discussed considering various effects of GGBFS, tensile and compressive stress levels, and cold joint.